Effect of glycerol on the electrical properties and phase behavior of cassava starch biopolymers (2012)
Films of different concentrations of glycerol/starch (G/S) blends were prepared and analyzed by impedance spectroscopy (IS), differential scanning calorimeter (DSC) and thermogravimetric analysis (TGA). The dc-conductivity of the films increases with increasing both the glycerol content and temperature. A power-law dispersive behavior of the frequency-dependent conductivity at high frequencies has been observed in all G/S films in the blend compositions prepared, similar to that observed in other solid ionic conductors and known as a “universal dynamic response”. The electrical conductivity enhancement is consistent with the subtle changes in the –OH glycerol groups coordination with the starch chains introduced by increasing the glycerol content and temperature. A stable single phase is revealed under the electrical measurement conditions up to approximately 100 °C for all concentrations, but the stability can be maintained up to higher temperatures (150°C) at glycerol concentrations below G/S = 0.4.